Transgender paradox : most frequent emotional disturbances during the transition. - Basante Ballesteros, Marian Sofía; Ortiz Quevedo, Jenny Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The issue of sexual diversity calls on society to reflect, recognise and accept other gender identities and their expressions. In this sense, the aim of this research is to recognise the most frequent psycho-emotional alterations of a transgender person during their gender transition between the ages of 10 and 19. The research process is framed within the qualitative approach and the documentary review methodology was used. The results showed that the emotional alterations in transgender people are not due to gender dysphoria, as it is not a pathology. In this sense, they are a product of the constant discrimination and abuse they face. Among the most frequent emotional disorders are depression, anxiety and stress. The importance of the family context as one of the most influential factors in shaping an adequate gender transition process is also discussed.